2011
DOI: 10.1073/pnas.1112660108
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosislipomannan blocks TNF biosynthesis by regulating macrophage MAPK-activated protein kinase 2 (MK2) and microRNA miR-125b

Abstract: Contact of Mycobacterium tuberculosis (M.tb) with the immune system requires interactions between microbial surface molecules and host pattern recognition receptors. Major M.tb-exposed cell envelope molecules, such as lipomannan (LM), contain subtle structural variations that affect the nature of the immune response. Here we show that LM from virulent M.tb (TB-LM), but not from avirulent Myocobacterium smegmatis (SmegLM), is a potent inhibitor of TNF biosynthesis in human macrophages. This difference in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
223
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(231 citation statements)
references
References 42 publications
6
223
1
1
Order By: Relevance
“…For example, mir-125 is downregulated in response to LPS or bacterial pathogens and one target of mir-125 is TNF-a. In macrophages, an additional function of mir-125 may be to ensure that the TLR pathway is turned off in the absence of microbial infection, while its downregulation in response to TLR triggering may be needed for the inflammatory response [48]. In this study, we also identified mir-125 in tilapia, which shared 100% sequence with other three kinds of fish.…”
Section: Discussionmentioning
confidence: 62%
“…For example, mir-125 is downregulated in response to LPS or bacterial pathogens and one target of mir-125 is TNF-a. In macrophages, an additional function of mir-125 may be to ensure that the TLR pathway is turned off in the absence of microbial infection, while its downregulation in response to TLR triggering may be needed for the inflammatory response [48]. In this study, we also identified mir-125 in tilapia, which shared 100% sequence with other three kinds of fish.…”
Section: Discussionmentioning
confidence: 62%
“…[146][147] There is emerging evidence that miRNAs could serve as cancer immunotherapy and could serve as therapeutic targets in TB. [148][149] Cytokines and proteases TNF-α is essential to granuloma integrity, macrophage antimicrobial activity and ROSmediated Mtb killing.…”
Section: Micro-rnamentioning
confidence: 99%
“…MiR-125b acts as a negative regulator of this pathway by reducing the levels of its target tumor necrosis factora 15,34 and, unusual for miRNAs, by enhancing the stability of the NF-kb inhibitor NKIRAS2 (KBRAS2) 35 ( Figure 3). Enhancement of the stability of a target gene transcript was described in several recent publications.…”
Section: Mir-125b In Hematopoiesismentioning
confidence: 99%